USE OF QUANTITATIVE DATA OF 3D SEISMIC EXPLORATION FOR DETECTION OF TRAPS OF HYDROCARBONS WITH IN THE NORTH SIDE OF THE DNIEPER-DONETSK DEPRESSION - Vyzhva, S.; Solovyov, I.; Мihalevich, І.; Kruhlyk, V.; Lisny, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Based on the results of numerous seismic surveys conducted on the areas and deposits of the northern side of the Dnieper-Donetsk depression, an appropriate strategy for detecting hydrocarbon traps in this region has been determined. This takes into account modern requirements for exploration and prospecting of gas and oil deposits. They consist in determining the probable zones of accumulation of hydrocarbons based on the analysis of the structural-tectonic model. At the same time, the use of direct hydrocarbon indicators to predict structural, lithological or combined traps is also a necessary element in solving this problem. It has been shown that an effective approach to detecting hydrocarbon traps in this region is attribute analysis using seismic attributes such as seismic signal envelope, acoustic impedance or relative acoustic impedance. In most practically important cases, the analysis of the distribution of values of these attributes was sufficient to solve geological problems. At the same time, an example of extracting additional useful information on the spatial distribution of hydrocarbon traps from volumetric seismic images obtained from seismograms of common sources with a limited range of seismic angle inclinations is given. To analyze the distributions of seismic attribute values it is recommended to use geobody technology as the most effective one when using volumetric seismic data. Depending on the combination of seismic attributes involved in the analysis, the distributions of different properties of rocks are determined, in particular the zone of increased porosity or the presence of hydrocarbons. Analysis with the simultaneous use of several seismic attributes allows to directly identify hydrocarbon-rich geological bodies with high porosity and the like. The paper presents examples of detection of hydrocarbon traps in the areas and deposits of the northern side of the Dnieper-Donetsk depression, which are confirmed by drilled wells. An example of providing recommendations for wells drilling using the distributions of values of different seismic attributes is given. Generalizations are made on the distribution of promising areas for the presence of hydrocarbons on the northern side of the Dnieper-Donetsk depression and the ratio of this distribution with the identified structural elements of the geological environment.
Keywords: seismic exploration; seismic images; hydrocarbon traps of different types; seismic attributes; geological bodies; direct hydrocarbon indicators